Esophageal Cancer Clinical Presentation: Trends in the Last 3 Decades in a Large Italian Series. Issue 1 (January 2018) - Cavallin, Francesco; Scarpa, Marco; Cagol, Matteo; Alfieri, Rita; Ruol, Alberto; Sileni, Vanna Chiarion; Ancona, Ermanno; Castoro, Carlo
Abstract : Objective: The aim of this study was to investigate trends in patients' characteristics and comorbidities in esophageal cancer (EC) patients. Background: Identifying changing pattern is essential to understand and predict further changes and to plan surgical procedures and resource allocation. Methods: Trends in patients' characteristics and comorbidities were evaluated in 4440 EC patients at the Center for Esophageal Diseases in Padova, Italy, during 1980 to 2011. Joinpoint regression analysis was performed to evaluate trends and to estimate annual percentage changes (APCs). Results: During the study period, there has been a statistically significant increment of the rate of esophageal adenocarcinoma (APC 3.70). The rates of elderly and of asymptomatic patients increased over time (APCs 0.98 and 6.24), whereas the rates of malnutrition, alcoholic drinking, and gastric ulcer decreased (APCs −1.50, −1.72, and −5.20). Reflux rate increased until 1997 and decreased thereafter (APCs 6.96 and −4.48), whereas the rate of Barrett esophagus increased until 1992 (APC 35.84) and then leveled. The rates of patients with previous neoplasms increased over time (APCs 3.22 and 4.86). There have been significant changes in systemic comorbidities, with an increase of hypertension and cardiac disease (APCs 7.56 and 1.86) and a decrease of advanced liver disease and pulmonary disease (APCs −2.67 and −1.74). Conclusion: The current EC patient has more often an esophageal adenocarcinoma and is more frequently elderly, asymptomatic, a survivor of previous neoplasms, and a patient with hypertension and cardiac disease than 30 years ago. On the contrary, malnutrition, alcoholic drinking, gastric ulcer, pulmonary disease, and advanced liver disease decreased.